Analysis of Factors That Cause Accidents in The Construction of 6 Inner City Toll - Sunandar Ali; Mohammad Sobirin; Rina Fatimah Agustin (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Occupational safety and health factors greatly influence the number of work accidents for construction workers from a project. Ignoring these factors has been shown to result in high work accidents in construction projects. Therefore, this study aims to determine the dominant factors that cause work accidents to construction workers in the 6 Inner Toll Road Project. The stage of this research is a study of the various existing literature to determine the variables that will be used. The next stage is designing a research questionnaire and then collecting data by distributing questionnaires with the simple random sampling method. The data obtained from the questionnaire were processed using statistical calculation software and then explained through quantitative analysis and to determine the dominant factors that influence construction worker accidents, multiple linear regression analysis was used including validity and reliability tests, classical assumption tests, and regression tests. The results of this study indicate that the independent variables of the factors that influence construction worker accidents simultaneously and partially have a positive effect on the construction worker accident variable, where the influence of dominant variables is 0,009 X.P.5 , 0,008X. P.6 , 0,010X. P.11 , 0,002X. E.4 , 0,008X. E.5 , 0,004X. E.7 , 0,004X. R.7 , 0,008X. R.9 and 0,004X. R.13. So that if the independent variable increases, construction work accidents will increase.